THE COMMUNICATIVE ACTIVITIES IN â€œBRIGHT AN ENGLISHâ€ TEXTBOOK - Jaya Saputri, Nova (English Language Education Program, Faculty of Education and Teacher Training, Sulthan Thaha Saifuddin State Islamic University of Jambi, 2022)
The importance and need to have communicative skills in English, teaching materials (textbooks) play an important role in teaching English. This study was conducted to determine whether the textbook is in accordance with the communicative activities proposed by Richards and Rodgers in the textbook